Systematic Review: The Relationship of Spouses’ Support and Postpartum Depression - Sinta Effelia Agatra; Ira Titisari; Indah Rahmaningtyas; Finta Isti Kundarti (STIKes Patria Husada Blitar, 2023)
Postpartum depression is a mental health problem experienced by mothers at 4 weeks after giving birth which is characterized by feelings of sadness, decreased mood, feelings of failure or guilt, and even suicidal ideation, one of which is due to lack of husband support. To analyze the incidence of postpartum depression, the provision of husband support, and the relationship between providing husband support to the incidence of postpartum depression. This study used a systematic review design by tracing journal articles through the database like as Proquest, Garuda Portal, PubMed, and Science Direct with the publication year from January 2012 - January 2022 and discussing husband support and the incidence of postpartum depression, and using Indonesian and English. The keywords used in national journal were